Primates of Western Uganda - Newton-Fisher, Nicholas E.; Newton-Fisher, Nicholas E.; Notman, Hugh.; Notman, Hugh.; Paterson, James Durward.; Paterson, James Durward.; Reynolds, Vernon.; Reynolds, Vernon. (Developments in Primatology: Progress and Prospects,, 2006)
Written by an international array of primatologists, this volume provides a series of scientific accounts with topics that range from taxonomy and biogeography to ecology, behavior and physiology, and ultimately, to conservation. The species studied range from nocturnal strepsirrhines to chimpanzees and mountain gorillas. Every study is new, published here for the first time. Together they provide a collection of fresh discoveries and insights, and this book reflects both current patterns of reseach and the diversity of the primates of western Uganda.